Prevalence of post COVID-19 condition and associations with risk factors among U.S. adults: 2023 Behavioral Risk Factor Surveillance System - Heath, Gregory W.; Levine, David; Oppong, Gloria; Alghader, Majdi (Frontiers in Public Health, 2025)
IntroductionDuring the COVID-19 pandemic, between 12 and 20% of US adults were identified as having post-COVID-19 condition, commonly referred to as ‘Long COVID’. These individuals maintained symptoms of COVID-19 for 3 months or longer following their illness but lacked an active infection. Using the Center for Disease Control’s 2023 Behavioral Risk Factor Surveillance System, our hypotheses were that adults who did not meet the 2018 Physical Activity Guidelines for Americans for aerobic and strengthening activities, those not fully vaccinated against COVID-19, and those with certain non-communicable diseases would be at greater odds of reporting post COVID-19 conditions.MethodsThe association of post COVID-19 conditions were examined among the 46.4% of adults 18 years and older who had tested positive for COVID-19 (n = 201,248), with a subset these adults reporting post COVID-19 conditions (n = 27,074, 13.6%). Univariate and logistic regression analyses were conducted using SPSS (v29) for complex samples. Univariate analyses were initially conducted on both behavioral risk factors and multiple non-communicable diseases. Subsequently, a series of logistic regression analyses controlling for age, sex, race/ethnicity, and educational attainment were carried out to compare the outcome variable of post-COVID-19 conditions with the exposure variables of (1) not meeting the Physical Activity Guidelines for Americans, (2) not being fully vaccinated, or (3) having the non-communicable diseases of overweight/obesity, coronary heart disease, asthma, or hypertension.ResultsAdults (n = 13,449; 12.2%) who did not meet the Physical Activity Guidelines for Americans were at greater odds of reporting post COVID-19 conditions (aerobic activity – OR = 1.19, 95% CI 1.06, 1.33, p < 0.0001; strengthening activity – OR = 1.02, 95% CI 1.00, 1.03, p < 0.001) compared with those meeting the guidelines. Respondents who were not fully vaccinated (≤ 3 vaccinations) were at greater odds of reporting post COVID-19 conditions (OR = 1.42, 95% CI, 1.24, 1.49, p < 0.0001) compared with those reporting ≥4 vaccinations.DiscussionThe present findings support the hypothesis that adults who were female, did not achieve the Physical Activity Guidelines, were not fully vaccinated, and had certain non-communicable diseases demonstrated a stronger association with reporting post COVID-19 conditions following COVID-19 infection.